Family with Parents Abroad Through the Prism of Multilocality - Juozeliūnienė, Irena; Leonavičiūtė, Živilė (Sociologija. Mintis ir veiksmas, 2009)
The article focuses on sociological research of Families with parents abroad as multilocal parents-children variations, situated in several households in different countries. At first theoretical background is discussed. Basing on the ideas of social construction families are viewed as multilocal social constructs. The article discloses that „delocation“ of familial partnerships from national context results in the demitologization of organic relationships between families and nation states. The issues of globalized identities, new sources of social stigma as well as application of various terms are discussed. The second part of the article focuses on the results of sociological research, carried out in the Lithuanian town Pabrade. The authors aim to answer the questions whether Families with parents abroad, forced by labour migration, are classified as families? What makes the social group be classified as a family? What is the social reception of Families with parents abroad and explanation of this reception?
Keywords: emigration; multilocality; families with parents abroad; conceptualization; social reception